Prevalence of Behavioral Risk Factors of Non Communicable Diseases among Adolescents of Higher Secondary Schools of Lalitpur District in Nepal - Shrestha, Soni; Paudel, Radha Kumari; Shrestha, Nisha (Journal of Advanced Academic Research, 2018)
Non Communicable Diseases are the biggest cause of death worldwide. There are eight major risk factors, out of which four of them are behavioral risk factors (tobacco use, harmful alcohol consumption, unhealthy diets and physical inactivity) and four of them are biological risk factors. The general objective of this study is to assess prevalence of behavioral risk factors of non-communicable diseases among adolescents. The study was conducted on students of higher secondary schools of Lalitpur. A descriptive cross-sectional study was conducted with the sample size 396. Structured questionnaire developed by STEPS SURVEY Nepal 2013 was used for data collection. Data management, analysis and interpretation were done using SPSS 20 version by calculating frequency and percentage. The prevalence of current tobacco (smoking) consumption was 17.2% and the prevalence of smokeless tobacco consumption was 8.1%. Current alcohol consumption was 14.4%. The prevalence of inadequate vigorous intensity activity was 58.3% and moderate intensity activity was 50.5%. The prevalence of fruit and vegetables consumption was 21.2% and 60.4% respectively. On the basis of findings of study it is concluded that use of tobacco products and alcohol was higher in male than female. All of the students consumed fruits and vegetables at least once a day but none of adolescents follow the consumption of fruits and vegetables as recommended by WHO. The adolescents were active as they involved in both vigorous and moderate intensity activity. The private schools students were less involved in physical activity as compared to public schools.